New Selection Algorithm on Priority Service for Certification Queue Service Information System in BARISTRAND - Rizky Dwi Nugroho; Anjik Sukmaaji; Endra Rahmawati; Arifin Pujiwidodo; Teguh Sutanto (JUITA : Jurnal Informatika, 2022)
Queue management for product certification of perishable goods is a major problem faced by the Surabaya Industrial Standardization and Research Institute (BARISTAND). The purpose of this study is to combine the use of the First in first out (FIFO), First Expired First Out (FEFO) and Least Shelf Life First Out (LSFO) methods into an automatic queuing system that can ensure effective service performance in queue management. This research was conducted using qualitative methods with observations to collect data and processes about how the product certification queue process flow at the Surabaya Industrial Standardization and Research Institute (BARISTRAN). The results show that the service only requires an average service completion time of 0.14 products per minute, meaning that every hour it can serve approximately 8.4 products. The conclusion of the research system has succeeded in determining the queue based on the use of the First in first out (FIFO), First Expired First Out (FEFO) and Least Shelf Life First Out (LSFO) methods, and customers can perform the tracking process to find out the certification process for the registered products.